2008
DOI: 10.1007/s10792-008-9193-7
|View full text |Cite
|
Sign up to set email alerts
|

Orbital blood flow parameters in unilateral pseudoexfoliation syndrome

Abstract: These findings suggest that ophthalmic artery hemodynamic parameters change in both eyes of unilateral XFS patients, illustrating out the systemic nature of the disease. We conclude that XFS decreases OA blood flow velocities and increases vascular resistance through progressive build-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 23 publications
0
29
0
6
Order By: Relevance
“…Similar results were obtained by Yüksel et al [4] We have suggested a value of 0.72 for RI to be the cut-off value for differentiation of PXS. The case in discussion had a left ophthalmic artery RI of 0.88 which is far above what we had reported for the unilateral PXS [5]. We believe that the attenuated retinal vessels and pale optic disc seen on the left fundus are a reflection of increased vascular resistance in the ophthalmic artery due to buildup of pseudoexfoliative material in vessel walls.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…Similar results were obtained by Yüksel et al [4] We have suggested a value of 0.72 for RI to be the cut-off value for differentiation of PXS. The case in discussion had a left ophthalmic artery RI of 0.88 which is far above what we had reported for the unilateral PXS [5]. We believe that the attenuated retinal vessels and pale optic disc seen on the left fundus are a reflection of increased vascular resistance in the ophthalmic artery due to buildup of pseudoexfoliative material in vessel walls.…”
Section: Discussionmentioning
confidence: 48%
“…We have previously shown that in unilateral PXS, the affected side has significantly higher mean ophthalmic artery RI (mean ± SD, 95% CI; 0.74 ± 0.04 cm/s, 0.72-0.75) compared to age-sex matched controls (0.69 ± 0.07 cm/s, 0.66-0.72; p=0.009) [5]. Similar results were obtained by Yüksel et al [4] We have suggested a value of 0.72 for RI to be the cut-off value for differentiation of PXS.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…24 Dayanir et al studied the ocular blood flow changes in patients with unilateral pseudoexfoliation syndrome between eyes clinically affected by pseudoexfoliation syndrome versus clinically unaffected eyes and controls. 46 In eyes affected by pseudoexfoliation material, the ophthalmic artery experienced decreases in the peak systolic and end diastolic velocities and increases in the resistive index compared to the control group. Moreover, comparison of the clinically unaffected eyes with the control group showed significant decreases in mean peak systolic velocity by 23% and in end diastolic velocity by 40% of the ophthalmic artery.…”
Section: The Ocular Vasculaturementioning
confidence: 97%
“…4 Literatürde PEX sendromunun azalmış oküler kan akımı ve iskemik oftalmik hastalıklar ile ilişkili bulunmuştur. [5][6][7] PEX sendromunun santral retinal ven oklüzyonu için risk faktörü olduğu bilinmektedir. 8 Son yıllarda, spektral domain optik koherans tomografi [spectral domain optical coherence tomography (SD-OCT)] ile ilgili gelişmeler koroid kalınlığını in vivo olarak ölçme imkânı sağlamış-tır.…”
unclassified